LEGAL PROTECTION FOR EMPLOYEE FROM BANKRUPTED COMPANY LAY OFF ACCORDING TO LAW NO. 13/2003 OF EMPLOYEEMENT POWER JO LAW NO. 11/2020 OF WORK CREATION - Dias Andalan; Fauziah Fauziah; Muhammad Fahruddin (Jurnal Hukum Jurisdictie, 2022)
In national development, the workforce has an important contribution to the progress of the nation, for that it is necessary to protect workers to ensure equal opportunities and treatment without discrimination to realize welfare for workers. The protection provided by the government to workers must guarantee workers to carry out work. Industrial relations which are the linkage of interests between workers/labourers and entrepreneurs, have the potential to cause disputes between workers and employers, disputes can occur because the company is bankrupt because it has maturing debts. Workers as one of the parties who have the right to pay their wages owed that arise because of the work agreement have the right to prioritize the payment of their receivables, that basically even though the company is in bankruptcy there are workers' rights that must be protected by the entrepreneur represented by the curator. Seeing the frequent occurrence of problems regarding layoffs that occur to workers / laborers due to bankrupt companies, the author focuses on the formulation of the problem, namely: 1. How is legal protection for workers who have been laid off in bankruptcy companies based on Law no. 11 of 2020 About Job Creation? 2. How to settle layoffs in bankrupt companies, case studies of decision no. 90./Pdt.Sus-Phi/2020Jkt.Pst Based on Law no. 13 of 2003 concerning the Employment of Jo. Law No. 11 of 2020 About Job Creation? In writing this thesis, the writer uses a normative juridical research method which aims to find out the settlement of disputes over the legal protection of workers who have been laid off due to bankrupt companies through collecting and analyzing data to obtain answers to the formulation of the problem. From the formulation of the problem raised in this paper, the author concludes that even though the company is in a state of bankruptcy, the workforce has rights in the form of severance pay, years of service and compensation for entitlements whose payment (preferred creditor) is regulated in the Act. Job creation, and basically layoffs occur in bankrupt companies just like layoffs in general, only the curator represents the company. In order to avoid the same problem, the curator must be guided by the law without ignoring the job creation law. For the settlement of case No. 90./Pdt.Sus-Phi/2020Jkt.Pst is in accordance with the theory which even though the company is in bankruptcy, workers have the rights regulated in Law No. 11 of 2020 concerning Job Creation.